2010
DOI: 10.1002/cncr.25252
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative DNA methylation analysis detects cervical intraepithelial neoplasms type 3 and worse

Abstract: BACKGROUND: DNA methylation may be used a potential biomarker for detecting cervical cancer. The authors of this report used quantitative methylation analysis of 4 genes in a full spectrum of cervical lesions to test its potential clinical application. METHODS: This hospital-based, retrospective, case-control study was conducted in 185 patients and included patients who had a normal uterine cervix (n ¼ 53), cervical intraepithelial neoplasm type 1 (CIN1) (n ¼ 37), CIN2 (n ¼ 22), CIN3 (n ¼ 24), carcinoma in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
89
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 57 publications
(127 reference statements)
4
89
1
1
Order By: Relevance
“…We and other research groups have observed that measurement of differential methylation of certain HPV CpG sites is useful for stratifying HPV type-specific risk [8,[11][12][13]19]. Additionally, methylation of CpGs in the promoters or introns of human genes has shown some value [5,6,9,14,20]. In earlier work we demonstrated that combining the measurement of human and HPV methylation might produce a better classifier than either alone [1].…”
Section: Introductionmentioning
confidence: 86%
“…We and other research groups have observed that measurement of differential methylation of certain HPV CpG sites is useful for stratifying HPV type-specific risk [8,[11][12][13]19]. Additionally, methylation of CpGs in the promoters or introns of human genes has shown some value [5,6,9,14,20]. In earlier work we demonstrated that combining the measurement of human and HPV methylation might produce a better classifier than either alone [1].…”
Section: Introductionmentioning
confidence: 86%
“…Among these altered and methylated genes, the paired boxed gene 1 (PAX1) and sex determining region Y-box 1 (SOX1) were both highlighted (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Numerous studies have documented the promise of PAX1 or SOX1 DNA methylation in distinguishing patients with reactive atypia or CIN3+ (cervical intraepithelial neoplasia type III or worse) lesions from normal uterine cervixes (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). In order to make a comparison of the accuracy of DNA methylation and HPV DNA testing, we performed a comprehensive meta-analysis and evaluated the diagnostic performance of PAX1 and SOX1 methylation for cervical cancer screening.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, LMX1A methylation testing demonstrated great potential for cervical lesion screening with a sensitivity, specificity and accuracy of 0.77, 0.88 and 0.90, respectively (30). In the present study, the pyrosequencing method was used to confirm the methylation of the LMX1A gene in cervical epithelial malignant transformation, but it was hardly methylated in LSIL.…”
Section: Discussionmentioning
confidence: 58%